Social Criticism and Morality in "Subversif!" Drama by Faiza Mardzoeki as Literature Teaching Materials - Putri, Intan Listyaning; Andayani, Andayani; Wardani, Nugraheni Eko (Journal of Languages and Language Teaching, 2024)
The overarching goal of education extends beyond the mere attainment of competencies and academic standards; it encompasses a broader responsibility to cultivate students' awareness of their societal roles, obligations, and rights. This research, undertaken with the specific focus on the drama script "Subversive!" by Faiza Mardzoeki, aims to elucidate the manifestations of social criticism and morality within this literary work. Employing a qualitative research approach, this study hinges on document analysis as its primary methodological framework. Qualitative research, distinguished by its departure from statistical procedures and quantitative calculations, relies on the exploration of assumptions, broad perspectives, theoretical lenses, and a thorough examination of research problems. The research findings primarily unveil instances of social criticism embedded in political contexts and discernible moral dynamics between individuals. Notably, these insights derived from the drama script "Subversive!" serve as valuable material for the pedagogical realm, contributing to the understanding of literary texts in educational settings. This research contends that the implications of its findings extend to the realm of high school literature education, providing a foundation for educators to consider various aspects, types, and impacts of literary works. By delving into the social and moral criticisms encapsulated within these texts, educators can enhance the learning experience, prompting thoughtful reflection on societal constructs and the multifaceted roles literature plays. Additionally, the research underscores the pivotal role of teachers in facilitating this process, thereby emphasizing the broader educational significance of integrating critical perspectives into the study of literature.